Prishvin on Stalin’s Collectivization: Observations of a Contemporary - A. M. Podoksenov (Научный диалог)
This article examines the perspectives of M. M. Prishvin on the collectivization of agriculture, utilizing materials from his “Diary”, which have only recently entered scholarly discourse in the post-Soviet years. The choice of this topic is motivated by the ongoing relevance and intensity of discussions surrounding the Stalin era in Soviet society. The focus of this study is a previously unexamined aspect within Prishvin studies: the writer’s attitude toward the radical transformation of traditional Russian peasant life. It is demonstrated that Prishvin, on one hand, critiques the ruthless methods employed in implementing collectivization, while on the other hand, acknowledges the positive aspects of the economic reforms occurring in rural areas. The significance of Prishvin’s insights regarding the origins and causes of collectivization is further underscored by the fact that his conclusions often predate those of several later researchers of the Soviet period. Prishvin’s analysis of both subjective and objective factors influencing Stalin’s collectivization reveals him not only as a gifted writer but also as an exceptional thinker with a distinct perspective on the pressing ideological, political, economic, and sociocultural issues of his time.